2023
DOI: 10.1111/jch.14722
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota changes in patients with hypertension: A systematic review and meta‐analysis

Meiling Cai,
Lingyu Lin,
Fei Jiang
et al.

Abstract: Hypertension is a major public health issue worldwide. The imbalance of gut microbiota is thought to play an important role in the pathogenesis of hypertension. The authors conducted the systematic review and meta‐analysis to clarify the relationship between gut microbiota and hypertension through conducting an electronic search in six databases. Our meta‐analysis included 19 studies and the results showed that compared with healthy controls, Shannon significantly decreased in hypertension [SMD = −0.13, 95%CI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…to be associated with coronary arteriosclerosis and systemic markers of inflammation, independent of cardiovascular risk factors [ 58 ]. Systematic reviews and meta-analyses have also found an increased abundance of streptococcus in patients with hypertension [ 59 ] and NAFLD [ 60 ]. Additionally, streptococcus enrichment is found in the gastric biopsies and feces of patients with gastric cancer [ 61 , 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…to be associated with coronary arteriosclerosis and systemic markers of inflammation, independent of cardiovascular risk factors [ 58 ]. Systematic reviews and meta-analyses have also found an increased abundance of streptococcus in patients with hypertension [ 59 ] and NAFLD [ 60 ]. Additionally, streptococcus enrichment is found in the gastric biopsies and feces of patients with gastric cancer [ 61 , 62 ].…”
Section: Discussionmentioning
confidence: 99%